Game-based summative assessment in islamic education: Development,Validation and effectiveness of a crossword-based instrument - Sholehatul Akmalia; Dian Erlina; Fajri Ismail; Indah Wigati; Maryamah (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The rapid development of digital technology has encouraged the transformation of assessment practices toward more interactive and student-centered approaches; however, the use of game-based tools as formal summative assessment instruments remains limited, particularly in Islamic education. This study aims to develop, validate, and evaluate a game-based summative assessment instrument for Qur’an Hadith learning using the Crossword Labs platform. The research employed a Research and Development (R&D) design based on the ADDIE model and adopted a mixed-methods approach involving 92 Grade VII students, 3 teachers, and 5 expert validators. The developed instrument, referred to as the Qur’an Hadith Crossword Labs (QHCL), integrates assessment items into a crossword puzzle format to enhance engagement while maintaining measurement rigor. The results indicate that the instrument achieved high content validity, with Aiken’s V values ranging from 0.868 to 0.971, and strong reliability, with a Cronbach’s Alpha coefficient of 0.804. Furthermore, the effectiveness test showed a high level of performance, with an average effectiveness score of 3.95 (very effective) and students’ achievement scores reaching 91.92 and 96.71 in the respective schools. These findings demonstrate that the QHCL instrument is valid, reliable, and effective as a summative assessment tool. In conclusion, this study provides empirical evidence that game-based digital tools can be systematically developed into rigorous and engaging assessment instruments, offering both theoretical contributions to assessment research and practical implications for improving assessment practices in Islamic education